ANALISIS CURAH HUJAN UNTUK MEMBUAT KURVA INTENSITY-DURATION-FREQUENCY (IDF) PADA SUB DAS METRO - Ir. Ernawan S, MT; Yuda Al Qadr Latief (Media Teknik Sipil, 2013)
Ernawan S.1) , Yuda Al Qadr Latief2)1,2) Jurusan Teknik Sipil Universitas Muhammadiyah MalangAlamat korespondensi : Jl. Raya Tlogomas 246 Malang 65144AbstractHydrological conditions in Indonesia and elsewhere is typical, so not all the way and all the concepts can be used to solve the problem of hydrology in Indonesia, especially in the Upstream Brantas River precisely in Sub Watershed of Metro. Rain is an important input component in the hydrological processes. Rainfall characteristics of which are the intensity, duration, depth, and frequency. Intensity related to the duration and frequency can be expressed by curves Intensity-Duration-Frequency (IDF). IDF curves can be used to calculateflood plan to use a rational method.In this study, daily rainfall calculated by frequency analysis begins by determining the mean maximum daily rainfall, then calculate statistical parameter to choose the most suitable distribution. The time is long dominant rainfall event with the greatest frequency of rain events. The intensity is calculated by using the data of observation.Based on the analysis of the frequency of the rain turns to design return period 2, 5, 10, 20, 50 and 100 years in a row is 49; 70; 86; 111; 132 and 155 mm. The results showed that the amount of time the dominant rain events between 4-8 hours. IDF curves in sub watershed of Metro based on the data observations generally showed a pattern where the rainfall is always preceded by a high intensity then progressively decreases. Besides the greater the return period tend to have higher rainfall intensity. The results of this research could bedeveloped even if it may be modified in accordance with the specific conditions subwatershed of Metro.